Modulation of Plasma 25-Hydroxyvitamin D3 Level by Imatinib Mesylate in Patients with Chronic Myelogenous Leukemia: The Role of Uptake and Efflux Transporters - Mervat M. Omran, MD; Samia A. Shouman, PhD; Raafat Abdelfattah, MD; Heba S. Moussa, MD; Nadia A. Thabet, Msc; Marwa S. Hamza, PhD (Elsevier, 2022)
ABSTRACT: Background: Vitamin D deficiency is a common side effect of imatinib mesylate (IM) therapy. Transporter polypeptides involved in the disposition of IM may be required for maintenance of adequate vitamin D concentrations. Objective: The aim of the present work is to study the association between the plasma concentrations of IM and plasma 25-hydroxyvitamin (25[OH]) D3 with transporter genotypes in patients with chronic myelogenous leukemia. Methods: A total of 77 adult patients with chronic myelogenous leukemia treated with IM participated in this study. Peak and trough plasma IM and 25(OH) vitamin D3 concentrations were measured and compared to the results of single nucleotide polymorphisms of the efflux transporting gene ABCB1-1236 C>T and the uptake transporting gene OATP1B3-334 T>G. Multiple linear regressions were used to examine the associations between 25(OH) vitamin D3 concentrations and a number of patient characteristics, including responses to therapy. Binary logistic regression analysis was used to predict odd ratios for the clinical response to IM. Results: Plasma 25(OH) vitamin D3 concentration quartile values were: 25%, 8.2 ng/mL; 50%, 9.8 ng/mL; and 75%, 12 ng/mL. High IM peak concentration, being OATP1B3-334 T>G (TT), and/ or ABCB1-1236 C>T (CT) are associated with lower concentrations of 25(OH) vitamin D3. Moreover, IM peak concentration, IM trough concentration, and plasma concentration of 25(OH) vitamin D3 were associated with the clinical response to IM. Conclusions: vitamin D, IM concentration, as well as the genotype of OATP1B3-334 T>G, had an influence on the response of patients with chronic myelogenous leukemia.